Modification of clay mineral with 2-(3-(2-aminoethylthio)propylthio)ethanamine for removal of metals from water - Theeradit Phothitontimongkol (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007